Ectopic transient overexpression of OCT-4 facilitates BMP4-induced osteogenic transdifferentiation of human umbilical vein endothelial cells. (March 2020) - Kim, Seung Hyun L; Lee, Seunghun S; Kim, Inseon; Kwon, Janet; Kwon, Song; Bae, Taegeun; Hur, Junho; Lee, Hwajin; Hwang, Nathaniel S
Limitation in cell sources for autologous cell therapy has been a recent focus in stem cell therapy and tissue engineering. Among various research advances, direct conversion, or transdifferentiation, is a notable and feasible strategy for the generation and acquirement of wanted cell source. So far, utilizing cell transdifferentiation technology in tissue engineering was mainly restricted at achieving single wanted cell type from diverse cell types with high efficiency. However, regeneration of a complete tissue always requires multiple cell types which poses an intrinsic complexity. In this study, enhanced osteogenic differentiation was achieved by transient ectopic expression of octamer-binding transcription factor 4 ( OCT-4 ) gene followed by bone morphogenetic protein 4 treatment on human umbilical vein endothelial cells. OCT-4 transfection and bone morphogenetic protein 4 treatment resulted in enhanced expression of osteogenic markers such as core-binding factor alpha 1, alkaline phosphatase, and collagen 1 compared with bone morphogenetic protein 4 treatment alone. Furthermore, we employed gelatin-heparin cryogel in cranial defect model for in vivo bone formation. Micro-computed tomography and histological analysis of in vivo samples showed that OCT-4 transfection followed by bone morphogenetic protein 4 treatment resulted in efficient transdifferentiation of endothelial cells to osteogenic cells. These results suggest that the combination of OCT-4 and bone morphogenetic protein 4 on endothelial cells would be a reliable multicellular transdifferentiation model which could be applied for bone tissue engineering.